Hydrogeochemical Characteristics and Water–Rock Interactions of Coalbed-Produced Water Derived from the Dafosi Biogenic Gas Field in the Southern Margin of Ordos Basin, China. (8th June 2021) - Bao, Yuan; An, Chao; Wang, Chaoyong; Guo, Chen; Wang, Wenbo
Abstract : The hydrogeochemical characteristics of coalbed-produced water can provide insights into the sources of ions and water, the groundwater environments, hydrodynamic conditions, and water-rock interactions of depositional basins. To study the water-rock reaction process and reveal whether there is a microbial activity in the groundwater, a case of the Dafosi biogenic gas field was chosen by testing the ionic concentrations and hydrogen and oxygen isotopic compositions of coalbed-produced water and employing R-type cluster and principal component analyses. The results showed that Na +, Cl −, and HCO3 - are the principal ions in the coalbed-produced water, while the water type is mainly a Na–Cl. Due to the hydrolysis of HCO3 -, the pH in this region was controlled primarily by HCO3 - . As the main cation in water, Na + contributed substantially to the total dissolved solids. Na + is also related to the exchange between rock-bound Na + and Ca 2+ and Mg 2+ in water or surrounding rocks. The coalbed-produced water's oxygen isotopes displayed a characteristic 18 O drift and enrichment, indicating that the 16 O isotope in the water was preferentially exchanged with the coal organic matter. Early evaporation is also contributed to the enrichment of TDS (total dissolved solids) and 18 O in the water. The central part of the study area, including the Qijia anticline, was affected by the Yanshanian uplift and denudation and subsequently developed a water-conducting fissure zone and was recharged atmospheric precipitation; these conditions were conducive to the formation of secondary biogenic gas.